Public enterprise : selected readings - Turvey, Ralph (Harmondsworth : Penguin books, 1968)
This book comprise of papers by scholars that examine the concept (3z(Bpublic enterprise.(3y (BPapers include: recent developments in the theory of marginal cost pricing; in defence of public-utility price theory; peak-load pricing; investment criteria for public enterprise; the economics of system planning in bulk electricity; water supply; telephone services; electricity tariffs; British and American postal service; cross-subsidisation in coal; residential telephone service in Britain and state liquor monopoly.s
This book is one of several volumes added as a supplement to a small library on economic development presented by the economic development institute of the World Bank to various institutions in the developing member countries of the bank.
Bibliography: p. 378-379.
lje 12/12/18
Loans
Keywords: Government business enterprises; Public enterprise; United Kingdom; United States of America